Estudo da variação do perfil químico de citros com HLB e sadios, buscando informações sobre mecanismo de defesa - Bellete, Barbara Sayuri (Universidade Federal de São Carlos, 2014)
This paper describes the variation of the chemical profile study of citros after inoculation of the bacterium "Candidatus Liberibacter asiaticus", responsible for Huanglongbing (ex greening), one of the most serious diseases causing several losses in the Brazilian citrus industry. The bacterium "Ca. Liberibacter " was inoculated in seedlings of the" Valencia "(Citrus sinensis (L.) Osbeck) grafted on "Swingle" (Poncirus trifoliata x Citrus paradisi) and was evaluated the change of secondary metabolites by the development of analytical methods such as HPLC-UV, LC-MS/MS, LC-UVSPE- NMR and chemometric tools. The chemometric methods PCA and S-PLOT applied to data obtained in the studies by LC-MSE allowed to discriminate infected plants from healthy plants, and also allowed the characterization of the compounds that most contribute to this differentiation. By analyzing the change in the chemical profile of citrus studied by HPLC-UV-SPE-NMR, it was able to detect the change of some coumarins in the roots and stem from rootstock, and glycosides flavonoid in leaves, indicating that these compounds may be involved in defense mechanism of the plant, and may be acting as a Phytoanticipins. Aiming to better interpret this change observed, also performed a quantitative variation of some secondary metabolites, as coumarin identified in the roots, and flavonoids identified in leaves. This technique showed an increase of coumarins in infected plants, while there was a decrease in all the flavonoids in the leaves in infected treatment, indicating that the plant defense is in the roots. Finally, a phytochemical study of citrus was performed aiming obtain patterns compounds, and this study resulted in the isolation of 13 substances, from several classes of secondary metabolites.
Study of the chemical profile of health and infected citros plants with huanglongbing, aiming information on resistence mechanism
Keywords: Química orgânica; Cítricos; Huanglongbing (HLB); Greening; Fitoquímica; Candidatus liberibacter asiaticus; CIENCIAS EXATAS E DA TERRA::QUIMICA